Pengaruh Metode Role Playing Terhadap Hasil Belajar SKI Di Kelas VI MI Istiqomah Sako Kecamatan Pangean Kabupaten Kuantan Singingi Riau - Emelia Emelia; Arifmiboy Arifmiboy; Charles Charles; Darul Ilmi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
The research is motivated by the low grdae VI studensts of MI Istiqomah Sako in the subject of islamic cultural history. The can be seen from the low midtrem exam scores and the way of learning in the learning process of islamic cultural history. In the learning proces educators tend to only use conventional learning methods so that learning is less attractive to students. One effort that can overcome this is the learning process using the role playing methods to improve student learning outcomes. This study aims to determine how much influence the use of the role playing methods has on the the learning outcomes of islamic cultural history of students in calss VI MI Istiqomah Sako Pangean district Kuantan Singingi regency Riau. The research is a quantitative research with a quasi eksperimental type with the non Eqiuvalent control group design. The sample in this study was in class VI consisting of two experimental classed and the control class. The result of the study stated that the calculation of the hypothesis test using the SPSS t-tets. The result of the calculation is that the propability value is Sig.(2-tailed) 0.00<0.05 thet it is accepted. From these result it can be concluded that there is an influeence of the role playing methods on leraning outcomes of islamic cultural history in the material of Sunan Kalijaga in class VI MI Istiqomah Sako Pangean District, Kuantan Singingi Regency Riau